Country financial development and the extension of trade credit by firms with market power - Galil, Koresh; Shapir, Offer Moshe; Zeidan, Rodrigo (Journal of Banking & Finance, 2025)
Prior research on the impact of market power on firms’ willingness to extend trade credit has produced inconsistent results, highlighting a critical gap in understanding firm behavior. This study addresses this issue by analyzing a comprehensive dataset of industrial firms across 26 countries, focusing on how the relationship between market power and trade credit depends on a country’s financial development level. Firms with monopolistic power often restrict credit provision to improve cash flow. However, our findings reveal a U-shaped relationship, where monopolistic firms in countries with either underdeveloped or highly developed financial sectors are more likely to extend trade credit than those in mid-level financial systems. This highlights the moderating role of financial development in shaping the interaction between market power and trade credit behavior.